USING THE ENERGY OF SEA WAVES – BASIC PRINCIPLES - Trizlova, Neli (E-Journal VFU, 2025)
The energy from sea and ocean waves is a completely non-polluting and renewable energy source that does not emit greenhouse gases during operation. This makes it an attractive alternative to fossil fuels. The energy source (wind and water) is free, natural and inexhaustible. The basic principles of wave energy conversion are examined. A classification of the main wave energy converters is made and their principles of operation are indicated. Conclusions are drawn about the effectiveness of these systems.
Keywords: wave energy; wave energy converters